2021
DOI: 10.1002/ppul.25248
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Study of Cystic Fibrosis: 25 years of observational research

Abstract: The Epidemiologic Study of Cystic Fibrosis (ESCF) was a prospective observational study of over 32,000 people with cystic fibrosis (CF) from 250 clinical care sites in North America from 1994 to 2005. Begun as a pharmacovigilance study in connection with the approval of dornase alfa in 1993, ESCF was open to all people with CF treated at any participating site in the United States or Canada. In addition to obtaining safety and effectiveness data on dornase alfa, ESCF collected encounter‐based data to character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 67 publications
(183 reference statements)
0
6
0
1
Order By: Relevance
“…In conclusion, the e x vivo competition experiments demonstrated that the patients’ disease status, particularly the stage of lung disease, was more relevant for the microevolution of P. aeruginosa than the bacterial clone type or genetic repertoire. The clinical relevance of the chronic airway infections with P. aeruginosa in CF is documented in patient registries by the time course of lung function, lung morphology scores and the outcome of culture-dependent diagnostics of respiratory secretions, respectively ( Konstan et al., 2021 ; Muhlebach et al., 2021 ; Orenti et al., 2021 ). However, these biomarkers are not combined with the complex interface of host - pathogen interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the e x vivo competition experiments demonstrated that the patients’ disease status, particularly the stage of lung disease, was more relevant for the microevolution of P. aeruginosa than the bacterial clone type or genetic repertoire. The clinical relevance of the chronic airway infections with P. aeruginosa in CF is documented in patient registries by the time course of lung function, lung morphology scores and the outcome of culture-dependent diagnostics of respiratory secretions, respectively ( Konstan et al., 2021 ; Muhlebach et al., 2021 ; Orenti et al., 2021 ). However, these biomarkers are not combined with the complex interface of host - pathogen interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Cystic fibrosis (CF) is one of the most common severe monogenic traits in populations of European descent ( Bell et al., 2020 ; Shteinberg et al., 2021 ). Thanks to the continuous improvement of the symptomatic treatment programs ( Lopes-Pacheco, 2020 ; Konstan et al., 2021 : Schlüter et al., 2021 ) and the recent development of highly efficient CFTR modulator therapies (HEMT) ( Heijerman et al., 2019 ; Middleton et al., 2019 ; Barry et al., 2021 ; Zemanick et al., 2021 ) the quality of life and prognosis for CF patients have meanwhile substantively increased. However, the chronic airway colonization with opportunistic pathogens, particularly Staphylococcus aureus and Pseudomonas aeruginosa , are rather refractory to therapeutic intervention ( Muhlebach et al., 2021 ; Durfey et al., 2021 ) and will remain the major co-morbidity in people with CF for many years to come, albeit HEMT has recently been demonstrated to substantially reduce the bacterial load with these opportunistic pathogens (S.T.…”
Section: Introductionmentioning
confidence: 99%
“…However, inhaled antibiotics should be discontinued following successful eradication of an organism or when samples remain persistently negative following appropriate microbiological surveillance. Nationwide registries may serve as an important source of information on practice patterns and help to provide historical control populations for new therapies [ 62 ].…”
Section: Cf and Treatment With Inhaled Antibioticsmentioning
confidence: 99%
“…The publicly open NIH program announcement (PA-19-034) detailing the classification and identification of 390 understudied druggable genomes was utilized to acquire the list of 261 candidate genes encoding GPCRs and ion channels. The associated literature survey was performed until 9 December 2021, with emphasis on published title words with (1) ion channels since 2017 [4,5,[9][10][11][12][13][14]16,26,27,30,33,[39][40][41][42]44,[46][47][48]53,54,59,61,[69][70][71][72][73][74][75][76][77][78][79][80], (2) ion channel blockers since 2017 [41,[81][82][83][84][85][86][87][88][89][90]…”
Section: Database Literature and Open-access Softwarementioning
confidence: 99%
“…Ion channels function as a gate via opening or closing by extracellular ligands [4], transmembrane voltage changes [5], or intracellular second messengers [6,7]. Mutations in ion channels are either causative or contributory to the pathogenesis of numerous disorders, such as cystic fibrosis [8,9], long-QT syndrome of the heart [10][11][12][13][14], heritable hypertension (e.g., Liddle's syndrome) [15][16][17][18], hyperinsulinemia and hypoglycemia of infancy [19][20][21], hereditary nephrolithiasis (e.g., Dent's disease) [22][23][24], and certain hereditary myopathies [25][26][27].…”
Section: Introductionmentioning
confidence: 99%